Pendeteksi Penanggulanagan Awal Kebocoran Gas LPG dan Keabakaran Menggunakan Arduino - Jufrizel Jufrizel; Anwar Habibi (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
Since the Indonesian republic government planned the displacement of kerosene to LPG gas, as the material for the benefit of everyday without thinking about the dangers of LPG gas cylinders. But we can see at present many problems posed by LPG gas cylinders, for example, the number of gas cylinders exploding unnoticed because certainly the explosion of gas cylinders. Is it because of the use who do not understand how to use and the use of gas cylinders or gas cylinders that are distributed indeed quality is not good Therefore we need an appropriate technology to address the problem. That is a design tool to be designed is a detector and early containment leakage of LPG gas and fire point to overcome the danger of explosion and fire both on the gas cylinder or from other elements with the technology, the people who use LPG gas will be mengetahwi will the gas leak on the design in the performance of these tools use arduino controllers.Keywords: arduino, fire sensor, lpg sensor, smoke sensor, temperature sensor